Urinary Tract Infection (UTI) Still a Force to be Reckoned with - Rao M.V, Raghavendra; Ponnusamy, Kumar; Bala, Sireesha; Pallavi.T, Sripada; M, KrishnaSowmya.; C.J, Ramanaiah; Verma, Mahendra K.; Fateh, Amin; Nayakanti, Abraham; Babu. A, Sateesh (British Journal of Healthcare and Medical Research, 2018)
Burning pain ,frequent urge to urinate is the first sign of a UTI. It is due to bacteria in the urethra or bladder. Frequent urination is another red flag for an infection. Urine produces peculiar even foul odor and smoky, cloudy. Urine appears pinkish or reddish due to the presence of blood.Young women are commonly infected.Prostate hypertrophy is linked to male disease. It is affecting almost 4 million people in US alone. The chance of UTI is more in women.In females, it affects the bladder and urethra. Women who use diaphragms, spermicidal agents are more at risk. Menopause women are more vulnerable to infection. Infection of upper urinary tract,consisting of the kidney and pelvis ,is known as pyelonephritis.Infection of the lower tract may involve the bladder (Cystitis),urethra (Urethritis) or prostate (Prostatitis) Intercourse is common association of UTI. Catheters increase the risk.Obstruction of urinary flow increase the risk.Bacterial adherence favors persistence.Fever is usually absent.Enterobacteriaceae and gram positive bacteria appear with complications.Back and perirectal pain are the signs of UTI.Pyuria suggests UTI but not specific.Chronic disease is the source of cystitis.Kidney infection results in permanent kidney damage. Take plenty of water/fluids to flush out bacteria.Wipe front to back. This helps the spread of bacteria from the anus into the bladder. Decreased estrogen levels during menopause cause changes that make the urinary tract more susceptible to bacteria. Most patients with UTI have uncomplicated cystitis, which is one of the most common infections in the United States, especially in sexually active women. Escherichia coli is the most common cause of urinary tract infection. Staphylococcus saprophyticus is a frequent cause of cystitis in women, probably related to its occurrence as a part of normal vaginal flora. Klebsiella, Enterobacter, Proteus, and Serratia are the primary opportunistic and often nosocomial pathogens. Pseudomonas aeruginosa is an opportunistic pathogen and a major cause of hospital-acquired infections.